INTELLECT DEVELOPMENT IN THE GROWING-UP PROCESS - E. M. Revenko (Russian State Vocational Pedagogical University, 2015)
The research is aimed at studying the dynamics specificity of intelligence development in the growing-up process.The research methods involve the group intelligence tests for junior teens; R. Amthauer's students test (IST) adapted by L. A. Yasyukova; longitude and cross-section methods.The research findings demonstrate both the irregularity and conformity of intelligence development starting from the secondary school and up to the undergraduate university level. In the secondary school, there is a fast growth of quantitative characteristics of intellectual dynamics and verbal skills do minance. However in the high school, the qualitative competence-related changes prevail giving way to the non-verbal skills; and the given trend continues up to the undergraduate level.The author emphasizes the differences in intellect dynamics depending on the student's basic mental faculties: the school students with higher faculties demonstrate a higher intelligence dynamics, while the university students reveal quite the opposite trend of lower intelligence dynamics in groups with higher faculties. As a result, the obvious differences in students' intellect capacities in the secondary and high school become less evident at the university level.The author points out the novelty of differentiated analysis of intellectual indices dynamics, substantiating the assumption of individual typical patterns of intellect development.The research outcomes make a foundation for the theory of individual and typological options (trajectories) of intellect development, and guarantee a differentiated approach to students' education according to the rate and tempo specifics of intellectual maturity.